Estudio de factibilidad para la creación de una empresa productora y comercializadora de miel de abeja, cantón Quevedo, año 2015 - Pinargote Mendoza, Stalin Rafael (2015)
This research was conducted in the Canton Quevedo which has 173,575 inhabitants according to the population census of 2010, it consisted of market research, technical, economic, and projected five years term financial evaluation in order to give the investor a tool of support for the creation of a company that produces and markets honey. For registration information, a questionnaire was used to survey people Quevedo Canton to determine the criteria on quality, price that they prefer when eating honey. Also through technical study found that currently the producer and seller of honey company will have a demand for 112476 people in the canton Quevedo, plus 52% of respondents stated that if they would be willing to consume honey if the company launched the product to market, the company will plant a capacity of 10,500 kilograms of honey production, also started production with 20 hives. The company will have a Director, Secretary, Workers, Beekeepers and Sellers. The net present value had a positive value of $ 23.856.83 what the net return generated by the project updated. Therefore the project is feasible. The internal rate of return is 16%, which was higher than the market interest rate, so the project is feasible and viable from the economic point of view. The cost benefit ratio is determined by dividing the net profit for interest rate bank loan; achieving the target of $ 1.44 KEY WORDS Feasibility Production Marketing